Penerapan Aplikasi Akuntansi Dalam Pemberdayaan Bumdes Di Gampong Blang Pulo Kecamatan Muara Satu Kota Lhokseumawe - Dy Ilham Satria; Hilmi Hilmi (Asosiasi Dosen Akuntansi Indonesia, 2021)
Partners in this PKM activity are BUMDes, in Aceh called Badan Usaha Milik Gampong (BUMG), located in Gampong Blang Pulo, Muara Satu District, Lhokseumawe City, Aceh. The objectives of this PKM activity are 1) To help BUMG administrators have not been able to overcome the problems faced regarding BUMG financial governance, especially those based on accounting applications. 2) Assisting the community in maximizing the exploitation of existing opportunities quickly and precisely, especially regarding booming businesses. The method used in this PKM activity is a communicative approach followed by a Focus Group Discussion, then provided with provision and training on BUMDes Accounting Applications and Training on Creative Ideas in Usaaha and Marketing Strategies. The solution and output target to be achieved is BUMG Gampong Blang Pulo which is expected to be able to overcome the obstacles faced by BUMG administrators in terms of preparing financial reports and making it easier to make reports that have been done manually and to improve the Doorsmeer business unit that is under BUMG.